2016
DOI: 10.1093/beheco/arw090
|View full text |Cite
|
Sign up to set email alerts
|

Between- and within-individual variation in activity increases with water temperature in wild perch

Abstract: In contrast to a growing interest in the ecological implications of consistent individual differences in behavior, it is still unclear how consistent those differences are across environmental gradients, especially under ecologically relevant contexts and timescales. We investigated how individual variation in swimming activity of Eurasian perch (Perca fluviatilis) changes in response to natural fluctuations of water temperature as a proxy for an ecological gradient for ectothermic animals. Using an automated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 62 publications
4
49
1
Order By: Relevance
“…High-resolution telemetry has been applied in many research fields, such as animal personality in the wild (Harrison et al, 2015;Nakayama, Laskowski, Klefoth, & Arlinghaus, 2016;Taylor & Cooke, 2014) and correlations between movement and life history traits (Nakayama, Rapp, & Arlinghaus, 2017). When coupled with environmental data, high-resolution telemetry affords an opportunity to re-evaluate our current knowledge about the behaviour of free-ranging fishes in the wild and offer new insights.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution telemetry has been applied in many research fields, such as animal personality in the wild (Harrison et al, 2015;Nakayama, Laskowski, Klefoth, & Arlinghaus, 2016;Taylor & Cooke, 2014) and correlations between movement and life history traits (Nakayama, Rapp, & Arlinghaus, 2017). When coupled with environmental data, high-resolution telemetry affords an opportunity to re-evaluate our current knowledge about the behaviour of free-ranging fishes in the wild and offer new insights.…”
Section: Discussionmentioning
confidence: 99%
“…23 for exception). Laboratory-based behavioral assays will rarely represent how the very same individuals behave in the wild24, and so far due to the difficulty of tracking fishes over long periods of time in the wild, only a few papers have documented consistent individual heterogeneity in fish behavior in free-ranging individuals targeted by fishers232526.…”
mentioning
confidence: 99%
“…We found that environmental contexts influenced the spiders’ intra‐individual variability as spiders behaved more predictably in some contexts than in other contexts. Previous studies have shown that intra‐individual variability may vary across ecological contexts or environmental conditions (Briffa, ; Highcock & Carter, ; Nakayama et al, ; Pruitt, DiRienzo, Kralj‐Fišer, Johnson, & Sih, ). Here, we find that P. labiata increases the intra‐individual variability when they face conspecific intruders as compared to the context with the environmental change only.…”
Section: Discussionmentioning
confidence: 99%